First point of contact physiotherapy: a realist review and evaluation - Goodwin, Rob (2019)
Background General Practice, the cornerstone of the National Health Service (NHS), is experiencing increased patient demand and overstretched resources. Musculoskeletal health disorders (MSDs), such as back pain and hip pain, are common conditions. Almost all patients with MSDs consult their general practitioner (GP) as a first point of contact (FPC). Evidence exists that physiotherapy is an effective intervention for most MSDs.